Pengelolaan Akun Instagram sebagai Strategi Pembangunan Brand Awareness @torch.id - Shafa Fadhilah Hermawan; Anisa Diniati (Journal of Communication, Business and Social Science (JCOBS), 2024)
Torch is a traveling and daily apparel brand with the Instagram account @torch.id. The account as a part of the social mediaplatform Instagram is an effective media in building brand awareness. This research aims to analyse the managementof @torch.id account in building brand awareness. This research uses social media content management by Kominfoconsisting of people, objectives, strategy, and technology and three elements of brand awareness strategy by Kotler andKeller. This research uses qualitative approach through interview and observation techniques. The result of this researchshows that the management of social media account @torch.id in creating brand awareness is done through introducingthe products in feed posts, running campaigns by tap-in to communities, and through interactions with their audience